Blending macro- and micro-fibres to enhance the serviceability behaviour of UHPFRC. Issue 2 (3rd July 2018) - Visintin, P.; Sturm, A. B.; Mohamed Ali, M. S.; Oehlers, D. J.
Abstract: The incorporation of steel fibres into ultra-high performance fibre-reinforced concrete (UHPFRC) leads to an overall improvement in the tensile and compressive ductility of the material. At the serviceability limit, fibres bridging cracks in the tension region increase member stiffness and improve crack control. At the ultimate limit, fibres crossing concrete-to-concrete sliding panes increase compressive ductility and ultimate material strains. In this paper, a method is developed for assessing the effect of different fibre types on serviceability behaviour (tension stiffening and crack width), without the necessity of performing large-scale beam tests. As an example of this approach, a series of direct tension and tension stiffening tests are performed on UHPFRC with blended fibres to determine the optimal mix design. The direct tension and tension stiffening results are then used to predict the moment curvature behaviour of a beam allowing the direct comparison of each mix without the necessity of expensive beam tests.